Plasma endothelin-1 and adrenomedullin are associated with coronary artery function and cardiovascular outcomes in humans. (15th September 2019) - Theuerle, James; Farouque, Omar; Vasanthakumar, Sheran; Patel, Sheila K.; Burrell, Louise M.; Clark, David J.; Al-Fiadh, Ali H.
Abstract: Background: Endothelin-1 (ET-1) is a vasoconstrictor associated with cardiovascular disease, whereas adrenomedullin (ADM) is a vasorelaxant with cardioprotective properties. We sought to determine the relationship between plasma ET-1 and ADM with coronary circulatory function and long-term major adverse cardiovascular events (MACE). Methods: Thirty-two patients undergoing coronary angiography for chest pain were recruited. Baseline plasma ET-1 and ADM levels were measured. The index of microcirculatory resistance (IMR), coronary flow mediated dilatation (cFMD) and coronary flow reserve (CFR) were measured in a non-obstructed coronary artery. Patients were assessed for MACE over a median period of 8.8 years. Results: Plasma ET-1 levels correlated with IMR ( r  = 0.57; p  < 0.01) and ADM levels correlated with CFR ( r  = 0.50; p  = 0.04) and cFMD ( r  = 0.62; p  = 0.01). After adjustment for age, gender and cardiovascular risk factors, the association between ADM and cFMD ( β  = 0.79; p  < 0.01) and between ET-1 and IMR ( β  = 5.7; p  = 0.01) remained significant. IMR was higher, although not statistically significant, in patients with long-term MACE (17.9 ± 5.3 vs. 13.1 ± 6.0 units; p  = 0.14). In patients free of MACE, cFMD (9.3 ± 7.6 vs. 2.8 ± 5.0%; p  = 0.01) and plasma ADM levels (7.6 ± 5.3 vs. 4.0 ± 1.9 pmol/L; p  = 0.07) were higher. Conclusions: Plasma ET-1 and ADM were associated with measures of coronary microvascular and coronary conduit vessel function, respectively. Increased cFMD and elevated plasma ADM were associated with a cardioprotective effect. Highlights: Elevated plasma endothelin-1 correlated with increased coronary microcirculatory resistance. Elevated coronary microcirculatory resistance was associated with increased long-term MACE. Elevated plasma adrenomedullin was associated with increased coronary flow mediated dilatation (cFMD). Elevated plasma adrenomedullin and cFMD were linked to reduced long-term MACE.